A new species of Lobesia Guenée, 1845 from Thailand (Lepidoptera: Tortricidae: Oletheutinae) - Charoensub, Thipmanee; Pinkaew, Nantasak; Sanguansub, Sunisa (Zootaxa, 2018)
Lobesia bisacca Charoensub and Pinkaew, n.sp., is described from Thailand. Specimens were collected in light traps in Trat Province, eastern Thailand and were deposited in the Kasetsart Kamphaengsaen Insect Collection. The new species can be distinguished from all other congeners by the unusual, long, protruding process from the base of the sacculus in the male genitalia. Illustrations of the adult, male genitalia, and male secondary characters are provided.